Program for creative leadership development among the school administrators under the Office of Ubon Ratchathani Primary Educational Service Area 2 - Moonmee, Wipaporn; Namwan, Tharinthorn (Journal for Developing the Social and Community, 2024)
The purpose of this research was 1) to study a current condition, a desirable condition, and the need for developing creative leadership among the school administrators under the Office of Ubon Ratchathani Primary Educational Service Area 2 and 2) to design and develop the program for creative leadership development among the school administrators under the Office of Ubon Ratchathani Primary Educational Service Area 2. The research was performed in 2 phases as follows. Phase 1: The current condition, the desirable condition, and the need for developing creative leadership among the school administrators under the Office of Ubon Ratchathani Primary Educational Service Area 2 were studied. The sample group consisted of 140 administrators and teachers in the Office of Ubon Ratchathani Primary Educational Service Area 2, using the Krejcie and Morgan table to determine the size, and there were 5 experts to approve research equipment. Phase 2: The design and development of the program for creative leadership development among the school administrators under the Office of Ubon Ratchathani Primary Educational Service Area 2 were studied. The data was collected by interviewing the administrators acknowledged in creative leadership from 3 schools: 1) Ubon Witthayakhom School under the Office of Ubon Ratchathani Primary Educational Service Area 1, 2) Anuban Ban Nuea Khemarat School under the Office of Ubon Ratchathani Primary Educational Service Area 2 and 3) Anuban Phibun Mangsahan Vipakvittayakon School the Office of Ubon Ratchathani Primary Educational Service Area 3. The program appropriateness was evaluated by the 5 specialists specifically picked. The research tools were a questionnaire, an interview form and appropriateness and feasibility evaluation scale. The statistics used in the quantitative data analysis were mean, standard deviation, and PNI Modified. The results were as follows: The current condition of creative leadership among the school administrators under the Office of Ubon Ratchathani Primary Educational Service Area 2 was overall at moderate level. The desirable condition of creative leadership among the school administrators under the Office of Ubon Ratchathani Primary Educational Service Area 2 was overall at utmost level. The needs for developing creative leadership among school administrators ordered in descending, namely, creative thoughts, flexibility and adaptability, individuality concern, teamwork. Program for creative leadership development among the school administrators under the Office of Ubon Ratchathani Primary Educational Service Area 2 consisted of 6 components: 1) principle, 2) purpose, 3) content, 4) learning media, 5) development process and 6) learning assessment. There are 4 modules of content, namely, 1) creative thoughts, 2) individuality concern, 3) flexibility and adaptability, 4) teamwork. The development process comprises of 1) self study, 2) workshop, 3) observe activities, 4) training. Moreover, the results of assessing the appropriateness and feasibility of the program were at the highest level.